Distribution of GnRH and Kisspeptin Immunoreactivity in the Female Llama Hypothalamus - Berland, Marco; Paiva, Luis; Santander, Lig Alondra; Ratto, Marcelo Héctor (Frontiers in Veterinary Science, 2021)
Llamas are induced non-reflex ovulators, which ovulate in response to the hormonal stimulus of the male protein beta-nerve growth factor (β-NGF) that is present in the seminal plasma; this response is dependent on the preovulatory gonadotrophin-releasing hormone (GnRH) release from the hypothalamus. GnRH neurones are vital for reproduction, as these provide the input that controls the release of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) from the pituitary gland. However, in spontaneous ovulators, the activity of GnRH cells is regulated by kisspeptin neurones that relay the oestrogen signal arising from the periphery. Here, we investigated the organisation of GnRH and kisspeptin systems in the hypothalamus of receptive adult female llamas. We found that GnRH cells exhibiting different shapes were distributed throughout the ventral forebrain and some of these were located in proximity to blood vessels; sections of the mediobasal hypothalamus (MBH) displayed the highest number of cells. GnRH fibres were observed in both the organum vasculosum laminae terminalis (OVLT) and median eminence (ME). We also detected abundant kisspeptin fibres in the MBH and ME; kisspeptin cells were found in the arcuate nucleus (ARC), but not in rostral areas of the hypothalamus. Quantitative analysis of GnRH and kisspeptin fibres in the ME revealed a higher innervation density of kisspeptin than of GnRH fibres. The physiological significance of the anatomical findings reported here for the ovulatory mechanism in llamas is still to be determined.